FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN UPAYA PENGENDALIAN KADAR GULA DARAH PENDERTA DIABETES MELLITUS TYPE 2 - Saputra, Anggi Happy; Putri, Dian Utama Pratiwi; -, Febria Listina; Sari, Nova Nurwinda (Jurnal Ilmiah Kesehatan Media Husada, 2025)
Diabetes mellitus is a group of metabolic diseases that are characterized by hyperglycemia that occurs due to impaired insulin secretion, insulin action or both, diabetes mellitus is often referred to as a silent killer and often causes various impacts on sufferers. Knowledge, attitudes, behavior and family support are some of the factors that can trigger blood sugar levels in Diabetes Mellitus sufferers. The purpose of this study was to determine the factors related to efforts to control blood sugar levels in patients Diabetes Mellitus Type 2 at Puskesmas Kalirejo in 2024. This study uses a quantitative research type with a cross-sectional research design. Sampling in this study used a purposive sampling technique with a sample size of 78 respondents. Data analysis with univariate analysis and bivariate analysis with Chi-Square. The results showed that there was a significant relationship between Knowledge (p = 0.000), Attitude (p = 0.011), family support (p = 0.037) with efforts to control blood sugar levels in patients Diabetes Mellitus Type 2. Knowledge is most strongly related to efforts to control blood sugar levels in patients Diabetes Mellitus Type 2, namely Diabetes Mellitus patients who have less knowledge are 22 times more likely to be at risk of lack of efforts to control blood sugar levels in patients DM Type 2.